In vitro interactions of proton pump inhibitors and azoles against pathogenic fungi - Gao, Lujuan; Xia, Xuqiong; Gong, Xiao; Zhang, Heng; Sun, Yi (Frontiers in Cellular and Infection Microbiology, 2024)
In the present study, in vitro interactions of proton pump inhibitors (PPIs) and commonly used azoles against a variety of pathogenic fungi were investigated. A total of 67 strains, namely 27 strains of Aspergillus spp., 16 strains of Candida spp., and 24 strains of dematiaceous fungi, were studied. The results revealed that PPIs individually did not exert any significant antifungal activity. The combination of OME with ITC, POS, or VRC showed synergism against 77.6%, 86.6%, and 4% strains of tested pathogenic fungi, respectively, while synergism of OME/FLC was observed in 50% strains of Candida spp. Synergism between PAN and ITC, POS, or VRC was observed against 47.8%, 77.6% and 1.5% strains of tested fungi, respectively, while synergism of PNA/FLC was observed in 50% strains of Candida spp. Synergism of LAN with ITC, POS, or VRC was observed against 86.6%, 86.6%, and 3% of tested strains, respectively, while synergism of LAN/FLC was observed in 31.3% strains of Candida spp. Synergy of the combination of RAB with ITC, POS, or VRC was observed against 25.4%, 64.2%, and 4.5% of tested strains, respectively., synergism of RAB/FLC was observed in 12.5% of Candida spp.. Antagonism between PPIs with ITC or VRC was rarely observed in Aspergillus spp. and dematiaceous fungi. It is notable that PPIs combined with azoles showed synergy against azole resistant A. fumigatus, and resulted in category change of susceptibility of itraconazole and posaconazole against Candida spp.. In summary, the results suggested that PPIs combined with azoles has the potential to enhance the susceptibilities of azoles against multiple pathogenic fungi and could be a promising strategy to overcome azole resistance issues.